2017
DOI: 10.1371/journal.pone.0182622
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the antioxidant and antibacterial activities of different olive processing wastewaters

Abstract: Olive processing wastewaters (OPW), namely olive mill wastewater (OMW) and table-olive wastewaters (TOW) were evaluated for their antibacterial activity against five Gram-positive and two Gram-negative bacteria using the standard disc diffusion and thin layer chromatography (TLC)-bioautography assays. Disc diffusion screening and bioautography of OMW were compared to the phenolic extracts of table-olive brines. Positive activity against S. aureus was demonstrated. The optimization of chromatographic separation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 43 publications
1
32
1
1
Order By: Relevance
“…These results demonstrate the strong capacity of the fraction F5 to inhibit Campylobacter growth. According to the described results, recent studies have also demonstrated the antibacterial effects of phenolic and secoiridoid enriched fractions obtained from OMW on several bacterial pathogens, including gram positive and gram negative bacteria (Aissa et al, 2017;Belaqziz et al, 2017). Usually, the antibacterial effect is greater in grampositive than gram-negative bacteria, which is consistent with a thicker and more complex cell wall in the case of gram-negative bacteria (Leouifoudi et al, 2015;Obied et al, 2007).…”
Section: Accepted Manuscriptsupporting
confidence: 58%
“…These results demonstrate the strong capacity of the fraction F5 to inhibit Campylobacter growth. According to the described results, recent studies have also demonstrated the antibacterial effects of phenolic and secoiridoid enriched fractions obtained from OMW on several bacterial pathogens, including gram positive and gram negative bacteria (Aissa et al, 2017;Belaqziz et al, 2017). Usually, the antibacterial effect is greater in grampositive than gram-negative bacteria, which is consistent with a thicker and more complex cell wall in the case of gram-negative bacteria (Leouifoudi et al, 2015;Obied et al, 2007).…”
Section: Accepted Manuscriptsupporting
confidence: 58%
“…Additionally, numerous biologic activities have been ascribed to HT, although in some cases its mechanism of action has not been clarified. Of particular interest are the anti-inflammatory and antimicrobial properties of HT, which have been described in many diseases [ 28 , 31 , 32 , 33 , 34 , 35 , 36 ]. In particular, it has been reported that HT was able to inactivate the staphylococcal enterotoxin A, a key factor in the patho-physiology of animal mastitis [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Elevated HT concentration has also been detected in olive mill wastewater and leaf extract [ 18 ]. In particular, numerous beneficial activities have been attributed to HT and its application has been described in different diseases [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. From the molecular point of view, HT enhanced the Nrf2 pathway [ 25 , 26 ] and ameliorated the antioxidant activity of several enzymes such as superoxide dismutase (SOD), glutathione peroxidase (GPx) and catalase (CAT) [ 27 ].…”
Section: Introductionmentioning
confidence: 99%